(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence of Tegolophus califraxini (Keifer) is pointed out in Northern Italy. This species, noxious for the buds of Fraxinus excelsior L., was found for the first time in Europe.